Uso de compostagem de aguapé (Eichhornia crassipes) na produção de milho verde - (:unkn) unknown (Universidade Estadual de Goiás, 2012)
Water hyacinth (Eichornia crassipes) composting is an organic fertilizer rich in macro and micro nutrients. It possesses a great potential to replace chemical fertilizers in the production of corn to meet the nutritional demand of the plant. The study was conducted during the growing season of 2011 in the months of June, July, August and September, in conditions of sprinkler irrigation in an Oxisol (LV) in the municipality of Pirenópolis, GO. The objective was to evaluate the effects of increasing doses of nitrogen (130 kg ha-¹ N) applied in form of water hyacinth compost (Eichornia crassipes) with and without cover and a formula NPK 04-14-08 with urea coverage This was done on some characteristics of corn, the hybrids AG1051. We used the experimental design of randomized blocks, an additional treatment (zero N) with five repetitions. Each treatment was divided into five replicates with a plot in each block. The tension of water in the soil was monitored by using tensiometers to do the irrigation management. We evaluated data on the variables: Mass of corn with straw and dehusked, crop yield, plant height (PH), ear insertion height (IEA) plant dry matter (PM) and amount of macro and micro nutrients in plants . The data was subjected to analysis of variance using the F test and comparison test of means (Tukey) at a significance level of 5%, using the Sisvar 5.1. program.The grain yield responded positively to N at a dose of 130 kg ha-1 in three treatments less the treatment without fertilization. From the collected data and the done observations it was found that the composting of Water hyacinth (Eichhornia crassipes) can be used as a nutrient source in the corn production to increase their productivity. In all treatments the plants had nutrient concentrations above the appropriate level. In the treatment where the compost was applied at one time it led to higher productivity of corn in absolute data.
Keywords: Adubação orgânica; Eichornia crassipes; Produtividade; Nitrogênio; Organic manure; Eichornia crassipes; Productivity; Nitrogen; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA; CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO; ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL